Interaction of (3‐Aminopropyl)triethoxysilane With Late ArN2 Afterglow: Application to Nanoparticles Synthesis. Issue 7 (25th January 2016) - Gueye, Magamou; Gries, Thomas; Noël, Cédric; Migot‐Choux, Sylvie; Bulou, Simon; Lecoq, Elodie; Choquet, Patrick; Belmonte, Thierry
Abstract : From results of in situ FTIR absorption and optical emission spectroscopy, the interaction of (3‐aminopropyl)triethoxysilane (APTES) with late ArN2 afterglow is shown to occur mainly with N atoms. They react preferentially with carbon from CH x groups in the precursor, leading to the synthesis of CN bonds. No production of NH radical is observed, demonstrating the lack of direct reaction between active nitrogen and APTES. The NH2 group is not affected by the afterglow. One of the CC bonds of the propylamine group in the APTES is likely broken. These nanoparticles present secondary amides due to reactions with active nitrogen. They are amorphous and react in air to produce a salt. Abstract : The synthesis of nanoparticles by interaction between a late ArN2 afterglow (3‐aminopropyl)triethoxysilane, a organosilicon compound containing one amine functional group, is shown to lead to an amorphous material containing amide functional groups produced by nitrogen atoms of the afterglow.